Head lice prevalence in suburban Bangkok, Thailand, after the COVID-19 pandemic and herbal shampoo treatment - Jirisuda Sinthusiri; Sirawut Sittichok; Hataichanok Passara; Mayura Soonwera (International Journal of Agricultural Technology, 2026)
The prevalence of pediculosis among 3,461 girls from 10 government kindergartens and primary schools in Ladkrabang district was 48.1% in the 1st semester (May- September 2022) and 44.6% in the 2nd semester (November 2022- March 2023), higher among primary school girls, at 51.8-55.4%, than in kindergarteners, at 30.2-33.1%. Over 80% of the infested girls came from a low-income family (<3,000 USD per year). The Zingiberaceae essential oil and shampoo treatments were highly effective with 100% cure rate for every infested girl after the 2nd treatment (on Day 10, after the 1st treatment on Day 1). Effective strategies for reducing head lice prevalence are improved living standards and head lice eradication by treatments with effective natural pediculicides and improved head lice educational program.
Keywords: Dermatological diseases and infestations; Insects and Parasite Interactions; Antibiotic Use and Resistance